Unemployment insurance in the United States : analysis of policy issues - O'Leary, Christopher J.; Wandner, Stephen A. (W.E. Upjohn Institute for Employment Research, 1997)
Discusses the unemployment insurance system in which programmes are operated by each state within the minimum standards established by the federal government.
Keywords: Unemployment insurance -- United States.; Unemployment insurance -- United States -- History.; Unemployment insurance -- Government policy -- United States -- History.; Assurance-chômage -- États-Unis.; Assurance-chômage -- États-Unis -- Histoire.; Assurance-chômage -- Politique gouvernementale -- États-Unis -- Histoire.; POLITICAL SCIENCE -- Public Policy -- Social Security.; Unemployment insurance; Unemployment insurance -- Government policy; United States; Arbeitslosenversicherung; Politik; Aufsatzsammlung; USA; Werkloosheidsverzekering.; Overheidsbeleid.; Labor & Workers' Economics.; Business & Economics.; unemployment benefit.; payment of benefits.; social security financing.; regional level.; national level.; unemployed.; long term unemployed.; employers participation.; contributions.; taxation.; payment system.; eligibility.; duration.; earnings replacement rate.; work incentive.; employment policy.; employment service.; statistical table.; Canada.; France.; Germany.; Italy.; Japan.; United Kingdom of Great Britain and Northern Ireland.; USA.; prestations de chômage.; paiement des prestations.; financement de la sécurité sociale.; niveau régional.; niveau national.; chômeurs.; chômeur de longue durée.; participation des employeurs.; cotisations.; fiscalité; système de paiement.; conditions d'ouverture des droits.; durée.; taux de remplacement.; incitation au travail.; politique de l'emploi.; service de l'emploi.; tableau statistique.; Allemagne.; Italie.; Japon.; Etats-Unis.; Royaume-Uni de Grande-Bretagne et d'Irlande du Nord.; prestaciones por desempleo.; pago de prestaciones.; financiación de la seguridad social.; nivel regional.; nivel nacional.; desempleados.; desempleado por largo tiempo.; participación de los empleadores.; cotizaciones.; tributación.; sistema de pagos.; elegibilidad.; duración.; tasa de sustitución.; incentivo al trabajo.; política de empleo.; servicio de empleo.; cuadros estadísticos.; Canadá; Alemania.; Francia.; Italia.; Japón.; Estados Unidos.; Reino Unido de Gran Bretaña e Irlanda del Norte.; History; bibliography.; graph.; recommendation.; bibliographie.; graphique.; recommandation.; bibliografía.; gráfico.